2016
DOI: 10.1590/1807-1929/agriambi.v20n8p702-708
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and potassium fertilization on ‘Caipira’ and ‘BRS Princesa’ bananas in the Ribeira Valley

Abstract: A B S T R A C T'BRS Princesa' (AAAB) and 'Caipira' (AAA) banana cultivars have similar sensorial features in comparison to the 'Maçã' banana. They are resistant to Panama disease, which allows them to grow in the Ribeira Valley, the largest banana plantation area in the São Paulo State. However, there is no information on how to fertilize crop under these edaphoclimatic conditions. This study aimed to evaluate the development and production of 'Caipira' and 'BRS Princesa' bananas, by applying four fertilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
(23 reference statements)
0
8
1
2
Order By: Relevance
“…The proposed approach is based upon water extraction from soil profile. The efforts related to field studies on the characterization of water extraction by banana are justified because this crop is an important agricultural commodity for many developing countries (Ding et al, 2013) and is highly demanding of water (Akinro et al, 2012) and fertilization (Nomura et al, 2016).…”
Section: The Root Zone Of Bananamentioning
confidence: 99%
“…The proposed approach is based upon water extraction from soil profile. The efforts related to field studies on the characterization of water extraction by banana are justified because this crop is an important agricultural commodity for many developing countries (Ding et al, 2013) and is highly demanding of water (Akinro et al, 2012) and fertilization (Nomura et al, 2016).…”
Section: The Root Zone Of Bananamentioning
confidence: 99%
“…The FHIA-17 (20) genotype showed the highest pseudo stems circumference mean (CPC = 79.19 cm), while Caipira (12) genotype showed the lowest mean (CPC = 52.90 cm) ( Table 2). Arantes et al 2017and Nomura et al (2016) also found low pseudo stems circumference values for the Caipira cultivar. The pseudo stems circumference is related to the vigor of the plant.…”
Section: Resultsmentioning
confidence: 89%
“…Similarly, Arantes et al (2017) found that the highest cultivars in all cycles were the Japira, Pacovan-Ken, and JV42-135 genotypes, and the shortest ones were the Grande Naine and Caipira genotypes. On the other hand, Nomura et al (2016) found, in the Ribeira Valley, high pseudo stems height values (> 4.5 m) in the Caipira cultivar, which is considered a substitute for Maçã cultivar. According to Santos et al (2006), the ideal height range for commercial bananas, is between 2.0 and 3.5 m.…”
Section: Resultsmentioning
confidence: 92%
“…Grand Naine verificaram que as maiores médias para altura do pseudocaule foram obtidos na dose de 400 kg de N ha -1 , correspondendo a 2,5 m, aos 240 DAT. Níveis adequados de adubação nesta fase tornam-se importantes pois sob condições de deficiência nutricional de N e K, as bananeiras apresentam senescência foliar, entre o período de produção de inflorescência e a colheita de cachos (Nomura et al, 2016). Segundo Santos et al (2006), plantas com menor porte também determina maior facilidade na operação de colheita, enquanto plantas muito altas podem tombar pela ação dos ventos.…”
Section: Altura De Pseudocauleunclassified